Isolation of Antibacterial, Nitrosylmyoglobin Forming Lactic Acid Bacteria and Their Potential Use in Meat Processing - Zhu, Yinglian; Yang, Qingli (Frontiers in Microbiology, 2020)
The use of nitrite as a colorant and preservative in meat processing is associated with health risks. This study aimed to isolate nitrite-substituting lactic acid bacteria for use as natural biological colorants and preservatives. Among the 106 strains isolated from fermented foods, two strains with excellent ability to convert myoglobin and metmyoglobin (Met-Mb) to red nitrosylmyoglobin (Mb-NO) were selected. The superior ability to form Mb-NO was confirmed through UV-visible spectrophotometry, fourier transform infrared spectrometry, electron spin resonance analysis, nitric oxide synthase activity assay, and Met-Mb reductase activity assay. The potent antibacterial activity was confirmed through biofilm and cytomembrane breakage of the indicator bacteria. Though performing 16S rDNA sequencing, they were identified as two different strains of Lactobacillus plantarum. Based on their favorable characteristics, their applications in the meat industry were further evaluated. This study identified a novel dual-function natural biological colorant and preservative to substitute nitrite in meat products. The application of the two strains would decrease the hazardous of nitrite to health.